Risk and the Pregnant Body - Lyerly, Anne Drapkin (The Hastings Center report, 2009)
Reasoning well about risk is most challenging when a woman is pregnant, for patient and doctor alike. During pregnancy, we tend to note the risks of medical interventions without adequately noting those of failing to intervene, yet when it's time to give birth, interventions are seldom questioned, even when they don't work. Meanwhile, outside the clinic, advice given to pregnant women on how to stay healthy in everyday life can seem capricious and overly cautious. This kind of reasoning reflects fear, not evidence.